(untitled) (Journal of Al-Wataniya Private University, 2023)
The study aimed to explain the composition of the capital structure that achieves better profitability and to clarify the best ratios that reflect the relationship of capital structure with profitability ratios in the banking sector to reflect the role and importance of this sector at the level of the Damascus Stock Exchange. By applying to both Islamic and commercial banks listed on the Damascus Stock Exchange using the panel data for the years 2008-2021.The study reached the following results: the effect of the capital structure measured (by the ratio of shareholders’ equity to total assets) on the profitability of Islamic banks (measured by the return on shareholders’ equity (ROE)) is significant, which indicates the net profit rate that investors reap from investing their money as a return on risk in investing their money. Hence the high level of safety in the field of investment in Islamic banks. In addition, the size of the bank, regardless of its commercial or Islamic activity, greatly affects its profitability, because the large companies may have a distinguished performance because they are more able to use economies of scale. The study also recommended the need for Syrian banks to increase their capital so that there is a kind of harmony between the size of the bank and its capital. As well as to expand its size by establishing multiple branches for it in the regions in addition to the governorates and to diversify the forms of banking services and diversify its investments. In addition, conducting studies and research based on linking the trading volume of the shares of these banks and their performance indicators to give effective details due to the importance of the trading volume in the financial market. Since there is a statistically significant relationship between the ratio of equity to total assets EAR and current liabilities to total assets LAR on the profitability of banks measured in earnings per share (EPS) . It is necessary to focus on increasing the use of these debts in financing the investments of banks, which will lead to an increase in their levels of profits.